Weigh feeder using steady state input. (2nd September 2011) - Sato, T.
The present paper proposes a new method for designing a weigh feeder control system. The model of a weigh feeder cannot be obtained accurately because its dynamic characteristics are time varying and its high frequency vibration modes are not easily identified. In the present paper, a weigh feeder is approximated as a first-order plus integrator system, and a self-tuning controller is designed on the basis of the approximated model to estimate its gain recursively. The purpose of this study is to design a controller to be actually employed in industry. To this end, a controller is assumed to consist of proportional gain for control error and steady state control input. As a result, the proposed controller has a simple structure and its controller parameters can be understood intuitively. Consequently, the proposed design method can be easily adopted in industry. Numerical and experimental results demonstrate its effectiveness.